Analisis Pemetaan Tingkat Kehadiran Siswa Dengan Metode K-Means Clastering - Dudih Gustian; M. Yosef Ismatulloh (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
The development of education is needed, among other things, to build the character of quality Human Resources (HR). School is one of the institutions that is responsible for the formation of character, especially the character of student discipline. Absence is a data collection activity to determine the number of attendees. Skipping an activity because students get bored while studying. Skipping school can have a negative impact on self and student achievement. At SMK Negeri 1 Surade there were fluctuations in attendance with various factors, out of 27 students there were 14 students with an attendance rate of 100%, and the ratio of all students was 51%. The benefit of this research is that it can encourage students to attend class. Meanwhile, schools can monitor easily and offer several alternative solutions for students with current problems. At the same time, parents can help monitor their child's learning process. By using the k-means clustering method, clustering can be made according to the results of the questionnaire. It is known that individual and internal class factor parameters require special attention, but in general students are still in the moderate category. After calculating from a number of 27 students, the first cluster consisted of 10 students (37%), the second cluster consisted of 16 students (59.3%) and the third cluster consisted of 1 person (3.7%)